Complex sleep : poems - Tost, Tony (Kuhl House poets., 2007)
Complex Sleep, Tony Tost's ambitious second book of poems, leaps upward with an astounding multiplicity of voices, utterances, and bursts. Each leap marks a sure and precise entry into a world of images, ideas, and sensations that is brand new - the true accomplishment of any poetic work. The octet of poems that compose Complex Sleep comprises a complex organism, audacious in scope, swiping at meaning via language as fragmented music. Tost takes on the problem of physical shape, reorchestrates phrases according to the alphabet, and writes himself into the hypnagogic state between wak.